Sporadic Insulinoma as a Rare Cause of Recurrent Hypoglycemia in Children - Hedyeh Saneifard; Ahmad Khaleghnejad Tabari; Maryam Kazemi Aghdam; Mohadese Musavi Khorshidi; Ali Sheikhy (Case Reports in Pediatrics)
Insulinoma is a rare pancreatic tumor in children and adolescents. As a result of insulin hypersecretion, signs and symptoms are more commonly consequences of the pathophysiologic responses to hypoglycemia. According to rarity of this tumor in children and nonspecificity of clinical presentations, diagnosis of insulinoma in this group of patients is usually delayed. Early diagnosis is very important for preventing neurologic damage. In this case report, we present the case of a 10-year-old boy with signs and symptoms of hypoglycemia and final diagnosis of insulinoma.